Equine Strangles: Management and Prevention - Sally DeNotta; Amanda House (EDIS)
Strangles is a disease caused by a bacterial infection of the upper airway and lymph nodes which is highly contagious in horse populations. This article describes the clinical signs, complications, diagnosis, treatment, management, vaccination, and prevention for non-veterinary audiences. Includes references. Originally published as "Understanding Equine Strangles: Signs of Disease, Management and Prevention" by Amanda M. House, August 2008; Revised October 2008. This update by Sally DeNotta.